The LFR-SWI/SNF complex: A chromatin wrench safeguarding cellular quiescence in the Arabidopsis root stem cell organizer - Shuge Wang; Jiayu Li; Mengmeng Li; Qiyan Fang; Xiaolei Shi; Long Yan; Qiang Chen; Xiaoyun Li; Muhammad Ans Aslam; Hao Zhang; Xigang Liu; Wenqiang Tang; et al. (Proceedings of the National Academy of Sciences, 2025)
The quiescent center (QC) resides in a reversible G 0 state in which cells are not actively dividing and yet retain their proliferation competence upon stimulation. How this quiescent state is molecularly defined and stably maintained is a fascinating question. Here, we uncover a dual role for LEAF AND FLOWER RELATED (LFR), a component of the SWITCH/SUCROSE NONFERMENTABLE (SWI/SNF) chromatin-remodeling complex, in maintaining quiescence of the QC. We demonstrate that LFR is recruited to the chromatin of core transcription factors (TFs) PLETHORA 1 (PLT1), PLT2, SCARECROW (SCR), and WUSCHEL - RELATED HOMEOBOX (WOX5) via physical interactions with them. Moreover, the autoregulatory binding of these TFs reciprocally requires LFR. Functioning as a chromatin wrench, LFR relaxes the chromatin at PLT1 , PLT2 , and SCR loci to sustain their positive autoregulation, thereby contributing to the prevention of QC cell division. Conversely, LFR compacts WOX5 chromatin to enforce negative autoregulation and simultaneously promotes CYCD3;3 expression to counteract WOX5-mediated repression, thus ensuring the proliferation competence of the QC. Furthermore, WOX5 throws a wrench into LFR binding at the CYCD3;3 promoter, establishing a regulatory circuit that precisely modulates CYCD3;3 expression, a D-type cyclin whose appropriate level is critical for QC quiescence. Consequently, the QC is maintained in a proliferation-competent but arrested state. Our findings establish the LFR-containing SWI/SNF complex as a key regulatory node that coordinates TF autoregulation with cell-cycle control to maintain QC quiescence.